Weed science research in India - BHAN, V M; KUMAR, SUSHIL (The Indian Journal of Agricultural Sciences, 2013)
Indian economy is primarily an agrarian one. Agricultural production depends on various factors and any set-back,in these factors severely aileets the yield of crops. Among all the pests (insects, animals, diseases and weeds) in India,weeds alone are responsible for one-third loss in crop production. Weeds in general reduce crops' yield by 20-30% butas the farmers adopt some kind of weeding practices lin their fields, a conservative estimate of 10% loss may be takenas more realistic. In India, till seventies, manual and mechanical removal was one af the best options available with thefarmers to manage weeds in their fields but'with the advent of labour cost, herbicides use started to get preference overmanual weeding particularly in Punjab and Haryana, and now good amount of herbicides is being produced and utilizedin India. In the seventies, biological control also started to take shape for weed control and in eighties good success wasachieved to control water-hyacinth (Eichhornia crassipes Solms). and water-fern (Salvinia molesta). This paper dealswith various weed problems and on going researches in different branches of weed science and different managementoptions fbr terrestrial, aquatic and parasitic weeds in context to indian situations. Issues, priorities and perspectives ofresearch for weeds management are also discussed.